Performance of a direct-expansion solar-assisted heat pump for domestic hot water production in Algeria - Benchamma, Sofiane; Missoum, Mohammed; Belkacem, Nefissa (Center of Biomass & Renewable Energy (CBIORE), 2024)
The focus of this study is to investigate the energy performance of a direct-expansion solar-assisted heat pump water heating system (DX-SAHPWH). The system consists of an unglazed solar collector-evaporator, which can absorb heat from solar energy and air ambient simultaneously, a condenser in the form of a coil immersed in a hot water storage tank, a thermostatic expansion valve and a hermetic reciprocating compressor. The performance of the heat pump system is evaluated using a developed mathematical model under Matlab code. The modelling method is based on lumped and distributed parameter approach of different system components. Numerical calculations were carried-out to study the influence of different parameters, such as ambient temperature, solar radiation intensity and polytropic index on the system performance. Additionally, in order to evaluate the long-term system performance, the system’s model was applied on a case study of a single-family building located in Djelfa (Algeria), which represents the coldest arid region of the country. The results showed that the solar radiation intensity and ambient temperature have significant effects on the heat pump performance. A COP of 5.9 and a collector-evaporator efficiency of 1.9 were obtained at high solar radiation of 850 W/m2 resulting in lower heating time (29 min). In addition, results revealed that the system can operate even at lower ambient temperature due to its ability to take advantage of heat from the ambient air. The results from the case study gave a COP ranging from 2.3 to 3.8, which enhance the promising adoption of this system in domestic hot water production to respond to people daily life needs with clean, abundant and renewable energy.